ChemInform Abstract: Highly Stereoselective [4 + 2] and [3 + 2] Spiroannulations of 2‐(2‐Oxoindolin‐3‐ylidene)acetic Esters Catalyzed by Bifunctional Thioureas. Issue 50 (December 2015) - Monari, Magda; Montroni, Elisa; Nitti, Andrea; Lombardo, Marco; Trombini, Claudio; Quintavalla, Arianna
Abstract: The first asymmetric organocatalytic strategy enabling access to both five‐ and six‐membered ‐nitro‐spirocarboxylic oxindoles containing up to six consecutive stereogenic centers is developed.